THE SOVEREIGNTY OF THE QURAN ACCORDING TO TAHA JABIR AL-ALWANI: AN ANALYTICAL STUDY - Hasballah Thaib, Zamakhsyari bin; Musolin, Mukhamad Hadi; Annisa, Vina (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
The study aims to elucidate Taha Jabir Al-Alwani's position, a prominent modern scholar, on the governance of the Quran as articulated in his work "The sovereignty of the Quran."  This study utilized an analytical and comparative methodology to elucidate the points of consensus and divergence between Al-Alwani and other scholars.  The study produced some significant outcomes which are: Al-Alwani articulated his perspective on Quranic sovereignty through the lens of "reading methodology" and "the construction of the Quran," contrasting with the conventional interpretations that emphasize political or jurisprudential dimensions. According to Al-Alwani, the administration of the Quran is characterized by epistemic and methodological principles rather than being solely political or legislative in nature.  The Quran serves as the foundational framework that Muslims ought to consult in the development of their sciences and knowledge, rather than being solely a source of regulation. Al-Alwani associated the essential aims of the Quran with sovereignty, which include: monotheism, purity, civilization, community, and invitation. By accomplishing these goals, the sovereignty of the Quran is manifested in both the individual and society. One criticism of Al-Alwani's perspective on governance is his overemphasis on the supremacy of the Quran to the detriment of the Sunnah, as evidenced by his advocacy for reconstructing Islamic methodology based solely on the Quran and his critique of intellectual traditions he perceives as having strayed from the authentic Quranic approach.  His critique of heritage occasionally transcends the scientific paradigm, and he tends to overstate his criticisms of heritage without proposing a viable alternative.